Analisis Faktor yang Berhubungan dengan Pemberian Susu Formula pada Bayi 0-6 Bulan - Oktova, Ravika (Jurnal Kesehatan, 2017)
Kinds of food pre-lacteal most given to the newborn are the formula milk of 79,8%, honey 14,3% and the water white 13,2% which includes milk non-formula, honey, water sugar, water tajin, banana smooth, coffee, tea sweetened, white water, rice smooth, pulp smooth (The Departement of Health, 2014&2015). The percentage of the scope of the lowest breastfeeding exclusive is at Rumbai Pesisir Health Center that is about 37,27 %. Research purposes were to know factor relating to the formula milk in infants age 0-6 month in Rumbai Pesisir Public Health Center Pekanbaru. The research was analytic design cross-sectional. The population of all the mother who the baby is 6-0 months was 1135 people. Samples were taken with accidental of sampling, as much as 92 people. Data analyzed by test chi-square (α<0,05). The results of statistical tests chi-square show that there is the correlation between knowledge, work and source of information by the formula milk feeding and there was no correlation between education with a formula milk feeding. Expected health workers to increase knowledge people such providing information of directives to the public about the formula milk influence in infants age 0-6 months.